Useful Algebraic Formulas

{ a }^{ m }\cdot { a }^{ n }={ a }^{ m+n }\\ \\ { a }^{ m }\div { a }^{ n }={ a }^{ m-n }\\ \\ { a }^{ 0 }=1\\ \\ { \left( ab \right) }^{ n }={ a }^{ n }{ b }^{ n }\\ \\ { \left( { a }^{ m } \right) }^{ n }={ a }^{ m\cdot n }\\ \\ { \left( \frac { ab }{ cd } \right) }^{ n }=\frac { { a }^{ n }{ b }^{ n } }{ { c }^{ n }{ d }^{ n } } \\ \\ { a }^{ \frac { m }{ n } }=\sqrt [ n ]{ { a }^{ m } } \\ \\ { a }^{ -n }=\frac { 1 }{ { a }^{ n } } \\ \\ { \left( \frac { a }{ b } \right) }^{ -n }={ \left( \frac { b }{ a } \right) }^{ n }\\ \\ { a }^{ \frac { 1 }{ 2 } }=\sqrt { a } \\ \\ \sqrt { a } \sqrt { b } =\sqrt { ab } \\ \\ \frac { \sqrt { a } }{ \sqrt { b } } =\sqrt { \frac { a }{ b } } \\ \\ \frac { a }{ b } \pm \frac { c }{ b } =\frac { a\pm c }{ b } \\ \\ \frac { a }{ b } \pm \frac { c }{ d } =\frac { ad }{ bd } \pm \frac { bc }{ bd } =\frac { ad\pm bc }{ bd } \\ \\ \left( a+b \right) \left( a+b \right) ={ a }^{ 2 }+ab+ab+{ b }^{ 2 }={ a }^{ 2 }+2ab+{ b }^{ 2 }\\ \\ \left( a+b \right) \left( a-b \right) ={ a }^{ 2 }-ab+ab-{ b }^{ 2 }={ a }^{ 2 }-{ b }^{ 2 }

GCSE + A Level Mathematics Proofs, Videos and Tutorials.